Pharmacological properties of phenyldiguanide and other amidine derivatives in relation to those of 5-hydroxytryptamine - Fastier, F. N. (1959)
Cats in which the coronary and allied chemoreflexes could not be obtained with small intravenous doses of 5-hydroxytryptamine were insensitive also to phenyldiguanide. In cats which responded to phenyldiguanide with reflex falls of blood pressure and heart rate, abolished by vagotomy, the effects of graded doses (5 to 150 μg./kg.) of phenyldiguanide bore a striking resemblance to those produced initially by 5-hydroxytryptamine in somewhat smaller doses. Differences in the cardiovascular responses to the two drugs are attributed to additional (non-reflex) actions of 5-hydroxytryptamine. The reflex actions of both drugs were blocked reversibly also by 2-naphthylguanidine (500 μg.). Certain other drugs (bufotenine, procaine, S-decylisothiourea) antagonized the depressor action of phenyldiguanide as well as the reflex depressor action of 5-hydroxytryptamine. Like 5-hydroxytryptamine, phenyldiguanide and certain other amidine derivatives caused pain when applied to the base of blisters in human subjects. Unlike 5-hydroxytryptamine, phenyldiguanide did not constrict perfused rat blood vessels or increase the tone of the rat fundal strip preparation of Vane (1957). Phenyldiguanide did not affect the sensitivity of these smooth muscle preparations to 5-hydroxytryptamine, but other amidine derivatives proved to be moderately strong antagonists of the vasoconstrictor actions of 5-hydroxytryptamine and of adrenaline. Unlike 5-hydroxytryptamine, phenyldiguanide did not produce gastric haemorrhage in the mouse. Phenyldiguanide did not prolong chloral hydrate sleeping time in mice by the same mechanism as did 5-hydroxytryptamine. Phenyldiguanide was not highly toxic to mice (LD50 being 240 mg./kg.). It is concluded that phenyldiguanide and certain other amidine derivatives act on sensory receptors which respond to 5-hydroxytryptamine, but that they show little pharmacological resemblance to 5-hydroxytryptamine in other respects.